Bacterial Calcium Carbonate Mineralization in situ Strategies for Conservation of Stone Artworks: From Cell Components to Microbial Community - Marvasi, Massimiliano; Mastromei, Giorgio; Perito, Brunella (Frontiers in Microbiology, 2020)
Calcareous stones have been widely used in artworks and buildings by almost all human cultures. Now, more than ever, the increased environmental pollution and global warming are threatening the stone cultural heritage. Weathering due to physical, chemical and biological factors results in monumental calcareous stone deterioration. These agents induce a progressive dissolution of the mineral matrix, increase porosity, and lead to structural weakening. Bacterial Calcium Carbonate Mineralization is a widespread naturally occurring process which in the last decades was proposed as an environmentally friendly tool to protect monumental and ornamental calcareous stones. The advantage of this treatment is that it mimics the natural process responsible for stone formation, producing a mineral product similar to the stone substrate. This mini review highlights the milestones of the biomineralization approaches with focus on in situ stone artworks protection. The strategies explored to date are based on three main approaches: i) the use of allochthonous and ii) autochthonous alive cells that, due to the bacterial metabolism, foster biomineralization; iii) the cell-free approach which uses fractionated cellular components inducing biomineralization. We discuss the challenging aspects of all these techniques, focusing on in-situ applications and suggesting perspectives based on recent advances.